Fully automated ultrasensitive digital immunoassay for cardiac troponin I based on single molecule array technology - Jarolim, Petr; Patel, Purvish P; Conrad, Michael J; Chang, Lei; Melenovsky, Vojtech; Wilson, David H (Clinical chemistry, 2015)
BACKGROUND: The association between increases in cardiac troponin and adverse cardiac outcomes is well established. There is a growing interest in exploring routine cardiac troponin monitoring as a potential early indicator of adverse heart health trends. Prognostic use of cardiac troponin measurements requires an assay with very high sensitivity and outstanding analytical performance. We report development and preliminary validation of an investigational assay meeting these requirements and demonstrate its applicability to cohorts of healthy individuals and patients with heart failure. METHODS: On the basis of single molecule array technology, we developed a 45-min immunoassay for cardiac troponin I (cTnI) for use on a novel, fully automated digital analyzer. We characterized its analytical performance and measured cTnI in healthy individuals and heart failure patients in a preliminary study of assay analytical efficacy. RESULTS: The assay exhibited a limit of detection of 0.01 ng/L, a limit of quantification of 0.08 ng/L, and a total CV of 10% at 2.0 ng/L. cTnI concentrations were well above the assay limit of detection for all samples tested, including samples from healthy individuals. cTnI was significantly higher in heart failure patients, and exhibited increasing median and interquartile concentrations with increasing New York Heart Association classification of heart failure severity. CONCLUSIONS: The robust 2-log increase in sensitivity relative to contemporary high-sensitivity cardiac troponin immunoassays, combined with full automation, make this assay suitable for exploring cTnI concentrations in cohorts of healthy individuals and for the potential prognostic application of serial cardiac troponin measurements in both apparently healthy and diseased individuals.
Keywords: lidé; Middle Aged; Adult; Heart Failure; troponin I; Female; srdeční selhání; Troponin I; Humans; imunoanalýza; Immunoassay; lidé středního věku; mužské pohlaví; mladý dospělý; Limit of Detection; Protein Array Analysis; ženské pohlaví; limita detekce; Young Adult; čipová analýza proteinů; Male; dospělí